(untitled) (Nigerian Journal of Pharmaceutical Research, 2021)
Background: Safe healthcare environments influence patients’ valuation of care received and impact on better health outcomes. It has been recognized that patients can contribute invaluably in improving the quality and safety of healthcare services they receive. Objective: To explore the perspectives of patients on their safety in healthcare. Methods: A qualitative study comprising of four (4) focus group discussions (FGDs) with six to eight participants was conducted in two public health facilities in Kaduna State, Nigeria. Patients admitted in medical wards (male and female) were recruited through a purposive sampling technique after obtaining their verbal informed consent to participate. A topic guide, containing open ended questions that explored patients’ opinions on their safety in healthcare was used for the discussions. All FGD sessions were recorded, transcribed and coded using thematic analysis. Results: The participants consisted of 15 females and 13 males in FGD sessions that lasted between 55 to 90 minutes. All participants were Hausa speaking, with varying levels of education. Six (6) themes were generated which the patients perceived to play a role in their safety in healthcare. These themes are: choice of hospital, patient satisfaction, patient experiences, patient engagement, communication openness and suggestions by patients for improvement. Conclusion: The findings of this study have highlighted both positive and negative perspectives of patients regarding their safety in healthcare. The patients provided some recommendations for areas where improvements are required for improved patient safety. These include infrastructural improvements, staffing, and availability of medicines, amongst others.